A four-component Fock-space coupled cluster investigation of the XMn(CO)5, (X = Cl, Br and I) photoelectron spectra - Nikoobakht, Behnam; Siebert, Max; Pernpointner, Markus (Chemical physics, 2017)
In this work we readdress the theoretical interpretation of the XMn(CO)5, X=Cl, Br, I photoelectron spectra by applying four-component Fock-space coupled cluster methods for their calculation. The final state characterization was based on group theoretical considerations of the contributing metal and ligand orbitals and the applied electronic structure methods extend earlier studies based on less demanding approaches. Energy level diagrams show the effect of spin-orbit (SO) coupling starting from scalar-relativistic results and especially for the heavy representative IMn(CO)5 a sizeable influence of the iodine p spinors on the spectral features and nonadditivity effects of SO and electron correlation contributions could be observed.